(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the cyclic use of different nitrogen sources on the morphometric characteristics and dry matter (DM) production of millet. A completely randomized design with five treatments was adopted: M0 - without nitrogen application; MU85 – only urea; MSA85 – only ammonium sulfate; MSA43U85 - ammonium sulfate up to 43 days and urea from 44 to 85 days and MU43SA85 - urea up to 43 days and ammonium sulfate from 44 to 85 days and seven repetitions. For DM production of the root and stem diameter at 65 and 85 days after seeding (DAS), there was an effect of nitrogen fertilization and cyclical use of the sources. The leaf area at 60 DAS was positively affected, with the MU85 and MSA43U85 treatments being superior. At 85 DAS, an effect of nitrogen fertilization was observed, however, with no difference between treatments that received nitrogen. The plant height variable, at 60 and 85 DAS, was affected by nitrogen fertilization and by the cyclical use of the sources, except for MSA85 and MU43SA85 treatment, respectively in the two phases. Fertilization and use of the sources affected the DM production at 60 DAS in all treatments, with the MU85 and MSA43U85 treatments being superior. At 85 DAS, DM production was higher in all treatments containing nitrogen. The cyclic use of different nitrogen sources positively affected the millet’s morphometric characteristics and dry matter production, with the MU85 and MSA43U85 treatments being the best results.